Fluorine‐Free Synthesis of High‐Purity Ti3C2Tx (T=OH, O) via Alkali Treatment. (25th April 2018) - Li, Tengfei; Yao, Lulu; Liu, Qinglei; Gu, Jiajun; Luo, Ruichun; Li, Jinghan; Yan, Xudong; Wang, Weiqiang; Liu, Pan; Chen, Bin; Zhang, Wang; Abbas, Waseem; et al.
Abstract: MXenes, 2D compounds generated from layered bulk materials, have attracted significant attention in energy‐related fields. However, most syntheses involve HF, which is highly corrosive and harmful to lithium‐ion battery and supercapacitor performance. Here an alkali‐assisted hydrothermal method is used to prepare a MXene Ti3 C2 T x (T=OH, O). This route is inspired from a Bayer process used in bauxite refining. The process is free of fluorine and yields multilayer Ti3 C2 T x with ca. 92 wt % in purity (using 27.5 m NaOH, 270 °C). Without the F terminations, the resulting Ti3 C2 T x film electrode (ca. 52 μm in thickness, ca. 1.63 g cm −3 in density) is 314 F g −1 via gravimetric capacitance at 2 mV s −1 in 1 m H2 SO4 . This surpasses (by ca. 214 %) that of the multilayer Ti3 C2 T x prepared via HF treatments. This fluorine‐free method also provides an alkali‐etching strategy for exploring new MXenes for which the interlayer amphoteric/acidic atoms from the pristine MAX phase must be removed. Abstract : Hochreines Ti3 C2 Tx (T=OH, O; 92 Gew.‐%) resultiert bei einem alkaliunterstützten Hydrothermalprozess ohne Einsatz von HF. Die gewichtsbezogene Kapazität des so erhaltenen Ti3 C2 T x mit OH/O‐Endgruppen (314 F g −1 ) übertrifft die eines HF‐geätzten Vergleichsmaterials um 214 %. Die Methode öffnet eine Route zu MXenen, in denen die amphoteren/aziden Zwischenschichtatome aus der reinen MAX‐Phase entfernt werden müssen.